Factors associated with heterosexual transmission of HIV to individuals without a major risk within England, Wales, and Northern Ireland: a comparison with national probability surveys. Issue 1 (3rd February 2006) - Gilbart, V L; Mercer, C H; Dougan, S; Copas, A J; Fenton, K A; Johnson, A M; Evans, B G
Abstract : Objective: To compare the prevalence of HIV risk behaviours reported by heterosexuals without major risks for HIV acquisition diagnosed with HIV in England, Wales, and Northern Ireland, with those of the heterosexual general population. Methods: Demographic and sexual behaviour data for heterosexuals (without major risks for HIV) aged 16–44 from the British National Surveys of Sexual Attitudes and Lifestyles in 1990 and 2000 were compared to 139 HIV infected individuals without major risks for HIV aged 16+ at diagnosis, interviewed between December 1987 and March 2003. Comparisons were made overall and separately for the early and late 1990s. Results: HIV infected heterosexual men without major risks were significantly more likely to report first heterosexual intercourse before age 16 (adjusted odds ratio (AOR): 2.75; 95% confidence interval (CI), 1.65 to 4.57), while both HIV infected heterosexual men and women reported greater partner numbers (AOR: men 2.44; CI, 1.4 to 4.05; AOR women 2.17; CI, 1.28 to 3.66) and never using condoms (AOR: men 7.97; CI, 4.78 to 13.3; AOR women 3.95; CI, 2.30 to 6.80) than the heterosexual general population. There is evidence to suggest that the two groups were more similar in their reporting of partner numbers in the late 1990s relative to the early 1990s. Conclusion: Heterosexual HIV infected individuals without major risks for HIV acquisition in England, Wales, and Northern Ireland are significantly more likely to report high risk sexual behaviours relative to the British heterosexual general population. However, these differences may have decreased over time, at least for the number of partners. Effective sexual health promotion, including the continued promotion of condom use, would impact on the rising rates of STI diagnoses and also prevent HIV transmission among the heterosexual general population.